The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4314/tjpr.v11i6.8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Genetic Basis of Tetracycline Resistance in <i>Staphylococcus aureus</i> from Pakistan

Abstract: Purpose: To determine the prevalence and genetic basis of tetracycline resistance in Staphylococcus aureus. Methods: One hundred and thirty (130) clinical isolates of S. aureus were collected from Khyber Teaching Hospital, Peshawar, Pakistan. Susceptibility to antibiotics (doxycycline, tetracycline and minocycline) was determined by Kirby-Bauer disc diffusion method with minimum inhibitory concentration (MIC) evaluated on Muller-Hinton agar as described by the Clinical and Laboratory Standards Institute (CLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…Tet(M) protects the bacteria from tetracycline by encoding ribosomal protective proteins which inhibits the binding of tetracycline to the ribosome. The tet(O)gene was not detected in any of the isolates, which correlates with studies conducted in Europe 19,20 and Pakistan 21 indicating that the gene is rare in S. aureus as previously reported by Bismuth et al 22 . Tet(L) was absent in all the isolates, which is akin to a study conducted in Europe(2000) on 400tetracycline-resistant clinical MRSA isolates in which tet(L) genes were detected in six (1.5%) isolates 19 .…”
Section: Journal Of Pure and Applied Microbiologysupporting
confidence: 88%
See 1 more Smart Citation
“…Tet(M) protects the bacteria from tetracycline by encoding ribosomal protective proteins which inhibits the binding of tetracycline to the ribosome. The tet(O)gene was not detected in any of the isolates, which correlates with studies conducted in Europe 19,20 and Pakistan 21 indicating that the gene is rare in S. aureus as previously reported by Bismuth et al 22 . Tet(L) was absent in all the isolates, which is akin to a study conducted in Europe(2000) on 400tetracycline-resistant clinical MRSA isolates in which tet(L) genes were detected in six (1.5%) isolates 19 .…”
Section: Journal Of Pure and Applied Microbiologysupporting
confidence: 88%
“…Tet(L) was absent in all the isolates, which is akin to a study conducted in Europe(2000) on 400tetracycline-resistant clinical MRSA isolates in which tet(L) genes were detected in six (1.5%) isolates 19 . Interestingly, no tet(K)was found in all the isolates screened even though tet(K) has been reported as a common and widely distributed gene in Staphylococcus aureus [19][20][21] . However, this was in agreement with a study conducted in South Africa where no tet(K) was found in 27 clinical MRSA isolates 5 .…”
Section: Journal Of Pure and Applied Microbiologymentioning
confidence: 94%
“…Infectious diseases are among the leading health problems, accounting for 41% of global disease Burdon [33]. The development of resistance by multidrug resistant (MDR) pathogens is a major problem in the chemotherapeutic management of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…tet genes are reported to be widely disseminated in the environment (Pallecchi et al, 2008;Di Cesare et al, 2012). The identification of tetracycline resistance determinants may be used as additional genotypic markers for the purpose of outbreak investigation and evolution of gene exchange (Koike et al, 2007;Ng et al, 2001;Ullah et al, 2012;Rico et al, 2014;Prichula et al, 2016).…”
Section: Antibiotic Susceptibility Profilementioning
confidence: 99%
“…The isolate SRLFDA/TIL-1/15 was examined for the presence of the tetracycline resistance encoding genes viz., tet (K) tet (L), following the primers and protocols of the previous researchers (Aarestrup et al, 2000;Garofalo et al, 2007;Ullah et al, 2012).…”
Section: Pcr Detection Of Tetracycline Resistance Genesmentioning
confidence: 99%